Emergências do corpo na cena teatral contemporânea: a potência das falhas, desativações e impossibilidades - Raquel, Fernanda (2017)
The thesis analyzes the constitution of the body in contemporary theatrical experiences where, through failures, deactivations and impossibilities, states that generate perceptual impacts, both in actors and spectators, are activated. Examples of those creation modes were selected works of the Japanese group Chelfitsch, Cia. Brasileira de Teatro and two plays directed by Carolina Mendonça, and also a practical experience, which proposes an alliance between academic and artistic research. The theoretical foundation relies on the indisciplinary methodology proposed by the corpomídia theory (KATZ and GREINER, 2005) which organizes networks between different areas of knowledge. Moreover, theoretical references from the field of theater and body studies are mobilized, as well as philosophical formulations of authors such as Giorgio Agamben (2008, 2014), Judith Halberstam (2011) and Jacques Derrida (2012). The expected result is to explicit the ways the operators - terms and concepts - are articulated to the bodily actions that cause destabilization in their usual functionality in life and aesthetic models given a priori, finding these same displacements, their political and performative potency